Organic nanotubes created from mesogenic derivatives. Issue 8 (26th June 2019) - Novotná, Vladimíra; Hamplová, Věra; Lejček, Lubor; Pociecha, Damian; Cigl, Martin; Fekete, Ladislav; Glogarová, Milada; Bednárová, Lucie; Majewski, Pawel W.; Gorecka, Ewa
Abstract : A facile route to prepare nanotubes from rod-like mesogens dissolved in typical organic solvents is reported. Abstract : A facile route to prepare nanotubes from rod-like mesogens dissolved in typical organic solvents is reported. For selected types of chiral rod-like molecules, nanotubes were formed from both enantiomers and racemic mixtures by slow evaporation from solution, regardless of the solvent, concentration or deposition type. The obtained supramolecular assemblies were studied using AFM, TEM and SEM techniques, and other experimental techniques (IR, UV-Vis spectroscopy and X-ray diffraction) were also applied. The difference in the surface tension at opposite crystallite surfaces is suggested as a possible mechanism for nanotube nucleation. We propose a quite new rolling-up mechanism related to the surface tension difference at opposite crystallite surfaces.